The hungry tide - Ghosh, Amitav (Harper Collins, 2006)
"The Hungry Tide is a contemporary story of adventure and unlikely love, identity and history, set in one of the most fascinating regions on earth. Off the easternmost coast of India, in the Bay of Bengal, lies the immense labyrinth of tiny islands known as the Sundarbans. For settlers here, life is extremely precarious. Attacks by deadly tigers are common. Unrest and eviction are constant threats. Without warning, at any time, tidal floods rise and surge over the land, leaving devastation in their wake." "In this place of vengeful beauty, the lives of three people from different worlds collide. Piya Roy is a young marine biologist, of Indian descent but stubbornly American, in search of a rare, endangered river dolphin. Her journey begins with a disaster, when she is thrown from a boat into crocodile-infested waters. Rescue comes in the form of a young, illiterate fisherman, Fokir. Although they have no language between them, Piya and Fokir are powerfully drawn to each other, sharing an uncanny instinct for the ways of the sea. Piya engages Fokir to help with her research and finds a translator in Kanai Dutt, a businessman from Delhi whose idealistic aunt and uncle are longtime settlers in the Sundarbans. As the three of them launch into the elaborate backwaters, they are drawn unawares into the hidden undercurrents of this isolated world, where political turmoil exacts a personal toll that is every bit as powerful as the ravaging tide."--BOOK JACKET.